IMPROVING ENGLISH READING ABILITY THROUGH LOOK AND SAY TECHNIQUE - anna fauziah (Journal of English Language and Literature (JELL), 2019)
The objective of the research is to improve English reading ability through Look and Say Technique at SDIT AL MARJAN, BEKASI. This study used action research method which involved two cycles. The population of this research was 27 of third grade students of SDIT AL MARJAN. Based on the data from the pre test, it shows that the students’ competencies in reading English is still low. After given treatment throughout the cycles (planning, acting, observing, and reflecting) in this study and the results of post tests, the student’s ability in reading English had been improved. Qualitative data analysis shows that the students were interested during the process. They enjoyed the learning and they were active in each part of the process. The students read better after the treatment. The result of the analysis is strengthen by quantitative data analysis which shows in cycle I, tₒ= 5,2, it means 2, 06< 5,2 and in cycle II, tₒ= 7,0 or 2, 06< 7,0. (t table 5% = 2, 06). Therefore, there is an improvement in English reading through look and say technique.